Isolation and characterization of cellulolytic fungi from decomposing rice straws - Shir, Nee Ong; Chin, Mei Lee (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rice straw is an agricultural waste that is normally produced after the paddy is harvested. Rice straw, which is high in cellulose content, makes it difficult to degrade. It is burnt away by most farmers as this method saves time and labor. However, the burning of rice straws could have a serious impact on the environment and human health in general. To overcome this, biodegradation using fungi should be applied in degrading the cellulosic waste. In this study, rice straws from Bagan Serai, Perak were collected. Decomposing of rice straws was prepared by adding coffee residue, cow and chicken dung, and phosphate fertilizer. A total of 18 isolates were isolated and purified from the sample and the isolates were brought further to macroscopic by observing the morphology. Morphological and microscopic characterization using a microscope was performed where the structure of the isolate was observed and their respective genus level was deduced. Among the 18 isolates, most of them were Aspergillus. Next, cellulase screening was done using carboxymethylcellulose (CMC) agar with Gram iodine staining. Isolate C7 showed the largest diameter of the halo zone at 48 h of incubation whereas isolate 4D has the most significant increase of halo zone in 24-h duration.